Sustainable synthesis of silver nanoparticles from Azadirachta indica: antimicrobial, antioxidant and in silico analysis for periodontal treatment - Barik, Binapani; Satapathy, Bhabani Sankar; Pattnaik, Gurudutta; Bhavrao, Desai Vijay; Shetty, Krishna Prasad (Frontiers in Chemistry, 2024)
This study explores using silver nanoparticles (AgNPs) to treat periodontal infection using Azadirachta indica leaf extract. The eco-friendly green synthesis process uses Azadirachta indica as a natural stabilizer and reducer, allowing AgNPs to be formed. Experimental AgNPs were characterized through transmission electron microscopy (TEM), Fouriertransform infrared spectroscopy (FTIR), Zeta potential, ultraviolet-visible spectroscopy (UV-Vis) etc. The antimicrobial, antioxidant potential of AgNPs was tested to identify its efficacy against periodontal infections. AgNPs were found spherical, nanosized 86nm. with positive surface -26.9 mV charge. TEM study depicted clear formation of discrete nanosize particles with smooth surface texture. Results showed strong antibacterial and anti-oxidant action of experimental AgNPs, preventing biofilm growth and bacterial viability. A higher binding affinity was observed between Quercetin and the selected protein, which is implicated in bacterial growth and biofilm formation on teeth. The study suggests that Azadirachta indica derived AgNPs could be a safe, efficacious, and eco-friendly alternative in place of conventional therapies to treat periodontal infection. Future in vivo studies are however warranted.